Analisis Pertanggungjawaban Pidana Terhadap Perusakan Hutan Di Kecamatan Batang Lubu Sutam Kabupaten Padang Lawas - Lubis, Muhammad Koginta; Siregar, Fitri Yanni Dewi (Jurnal Ilmiah Penegakan Hukum, 2024)
This research aims to find out the consequences and impacts of forest destruction carried out by individuals and corporations, either directly or indirectly, as experienced by the people in the Batang Lubu Sutam District, Padang Lawan Regency, North Sumatra Province, who experienced direct impacts as a result. from forest destruction, namely flash floods accompanied by thousands of logs of wood and soil. This research is empirical legal research by testing laws and cases of forest destruction which have a direct impact on society in the form of flash floods using a statutory approach and a case approach, the data obtained is then processed and An in-depth analysis was carried out regarding rules, literature study, normative approach, concept testing and drawing conclusions. The data is then presented in a descriptive analysis related to criminal liability for forest destruction. The results of the research show that the form of criminal responsibility for perpetrators of forest destruction, whether carried out by individuals or corporations, must be strictly enforced, namely in the form of prison sentences and fines as a result of these actions, such as the flash flood accompanied by thousands of logs of wood and land that occurred in Batang District. Lubu Sutam, Padang Lawan Regency, as a result of forest destruction